Motives for Moral Behavior Among Malay Muslim Students Secondary School - Maizura Yasin; Nur Surayyah Madhubala Abdullah; Samsilah Roslan; Nor Wahiza Abd. Wahat (TARBIYA: Journal of Education in Muslim Society, 2018)
AbstractThis paper provides an overview of the motives underpinning Malay Muslim secondary school students’ moral behavior in Malaysia in their daily life. The paper is based on a qualitative case study employing purposive sampling into the motives behind Malay Muslim students’ moral behavior. The study of eight Form Four Malay Muslim students in a school in Malaysia identified six themes associated with the motives for moral behavior. The findings illustrate that Malay Muslim students have different motives for their moral behavior and that these are linked to moral reasoning. It offers an insight into what motivates Malay Muslim students who are in a family structure where religion is a strong influence of their moral behavior. It illustrates how family background, religious values and personal experiences shape the reasons for behaving morally. A key implication of the findings for Moral Education is in educating students to behave morally, teachers in particular Moral Education teachers should consider that the motivation for the action may differ based on certain aspects of the student's background that influence their beliefs about what is right and good. Teachers should also identify the prevailing motives and their influences on students’ moral behavior by facilitating reflection on their behavior and the choice the right motives in morality.AbstrakPenelitian ini menyajikan gambaran tentang motif yang mendasari perilaku moral siswa Melayu Muslim pada sekolah menengah di Malaysia dalam kehidupan sehari-hari mereka. Penelitian ini menggunakan metode studi kasus kualitatif dengan menggunakan tehnik purposive sampling untuk menginvestigasi motif di balik perilaku moral siswa Melayu Muslim. Delapan pola dari Empat siswa Muslim Melayu di sebuah sekolah di Malaysia teridentifikasi memiliki enam tema yang terkait dengan motif perilaku moral. Temuan mengilustrasi bahwa para siswa Melayu Muslim memiliki motif yang berbeda pada perilaku moral mereka dan bahwa ini terkait dengan penalaran moral. Temuan penelitian ini menawarkan wawasan pada apa yang memotivasi para siswa Melayu Muslim ya ng berada dalam struktur keluarga di mana agama memiliki pengaruh yang kuat pada perilaku moral mereka. Temuan penelitian ini mengilustrasi bagaimana latar belakang keluarga, nilai-nilai agama dan pengalaman pribadi dapat membentuk alasan-alasan untuk berperilaku secara moral. Implikasi utama dari temuan Pendidikan Moral ini adalah dalam mendidik siswa untuk berperilaku secara moril, para guru terutama guru Pendidikan Moral harus mempertimbangkan bahwa motivasi untuk bertindak dapat berbeda berdasarkan aspek-aspek tertentu dari latar belakang siswa yang mempengaruhi keyakinan mereka tentang apa yang benar dan baik. Para guru juga harus mengidentifikasi motif yang berlaku dan pengaruhnya pada perilaku moral siswa dengan memfasilitasi refleksi diri atas perilaku mereka dan pilihan motif yang tepat di dalam moralitas. How to Cite : Yasina, M., Abdullah, Nur S. M., Roslan, S., Wahat, Nor W. A. (2018). Motives for Moral Behavior Among Malay Muslim Students Secondary School. TARBIYA: Journal of Education in Muslim Society, 5(1), 42-54. doi:10.15408/tjems.v5i1.9510.